THE USE OF ABUSIVE LANGUAGE IN THE FAST AND FURIOUS MOVIE (2001): PRAGMATICS STUDY - GUTAMA, SILTAS (2010)
This research paper is about abusive language in The Fast and Furious movie. The data of this research paper are the utterances of abusive language in The Fast and Furious movie. In The Fast and Furious movie, there are twelve words of abusive language. The objectives of this research paper are to know the formation, the meaning, and the function of abusive language in The Fast and Furious movie. The writer uses qualitative method to analyze the data. To analyze the data, the researcher identifies the form of abusive language then formed it to the form of abusive language according to six varieties of abusive language by Hughes, and the last the researcher finds the meaning and the function by using speech act theory. The results of the study are: (1) There are twelve data of abusive language in The Fast and Furious movie. They are shit, damn, bastard, fool, crazy, stupid, dog, skank, bitch, pant, ass and fuck. (2) The formation of abusive language according to six varieties by Hughes are word related to sex organ, word from excrement, word from mental illness, word from name of animal, and word related to sex activity. (3) The meaning of abusive language in The Fast and Furious movie are according to the situation where the utterance uttered by the speaker, and the function of abusive language are to express angry feeling, to degrade someone, sex activity, and to call someone.